Determinants of Economic Growth in East Nusa Tenggara Province - Putri Nastiti Wulandari; Lilis Siti Badriah; Nunik Kadarwati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2019)
This research aims to analyze the determinants of economic growth in East Nusa Tenggara Province, consisting of life expectancy, mean years of schooling, expected years of schooling, purchasing power, labor force participation rate, government investment, and number of tourists on economic growth, and to analyze the dominant variable influencing economic growth. The type of data used in this research is secondary data in the form of panel data with cross sections of 20 regencies/cities and time series for six years (2011-2016). The analytical tool used is panel data regression with fixed effect model. The results show that life expectancy, mean years of schooling, purchasing power, and government investment have a significant effect on economic growth. Whereas expected years of schooling, labor force participation rate, and number of tourists have no significant effect on economic growth. Life expectancy, mean years of schooling, purchasing power, labor force participation rate, government investment, and number of tourists simultaneously affect economic growth.Keywords: Economic Growth, Human Development Index, Labor Force Participation Rate, Government Investment, Number of Tourists.